Influence of Triatoma dimidiata in Modulating the Virulence of Trypanosoma cruzi Mexican Strains - E. Guzman-Marin; M. Jimenez-Coello; M. Puerto-Solis; A. Ortega-Pacheco; K. Y. Acosta-Viana (Interdisciplinary Perspectives on Infectious Diseases)
The epidemiology of Chagas disease is complex. There are different vectors and reservoirs and different clinical manifestations. In order to assess whether the biological behavior of three strains isolated in southeastern Mexico (H4 isolated from human, Z17 isolated from Didelphis sp., and V isolated from T. dimidiata) could be modified during passage through the vector T. dimidiata, the parasitemia curve, the amount of amastigote nests, and mortality of BALB/c infected with blood trypomastigotes of T. cruzi were evaluated. Strains were maintained in continuous passage from mouse to mouse and in animals infected with metacyclic trypomastigotes. The parasitemia curves were significantly different () between mice to mice and triatoma to mice groups in strains H4 and Z17, and was also observed fewer amastigote nests in cardiac tissue ( strain H4 with higher number versus all groups and Z17 between mice to mice and triatoma to mice) 45 days after inoculation. It is concluded that T. dimidiata influences in modulating the virulence of strains of T. cruzi in the region. Further studies of the intestinal tract of the insect in search for some protein molecules involved in regulating may clarify the virulence of the parasite.